The prevalence of musculoskeletal pain and use of painkillers among adolescent male ice hockey players in Finland - Selänne, H.; Ryba, T. V.; Siekkinen, K.; Kyröläinen, H.; Kautiainen, H.; Hakonen, H.; Mikkelsson, M.; Kujala, U. (Health Psychology and Behavioral Medicine: An Open Access Journal, 2014)
Participating in competitive sport increases the risk for injuries and musculoskeletal pain among adolescent athletes. There is also evidence that the use of prescription drugs has increased among sport club athletes. The purpose of this study was to evaluate the use of painkillers among young male ice hockey players (IHP) in comparison to schoolboys (controls) and its relation to the prevalence of musculoskeletal pain and problems during activities and sleeping. Information was gathered through a questionnaire, completed by 121 IHP and compared to the responses of 618 age-matched controls. Results showed that monthly existing pain was at 82% for IHP, and 72% for controls, though IHP had statistically more musculoskeletal pain in their lower limbs (56% vs. 44%), lower back (54% vs. 35%), and buttocks (26% vs. 11%). There were no group differences in the neck, upper back, upper limb, or chest areas. The disability index was statistically similar for both groups, as musculoskeletal pain causing difficulties in daily activities and sleeping was reported by a minority of subjects. Despite this similarity, IHP used more painkillers than controls (18% vs. 10%). Further nuanced research is encouraged to compare athletes and non-athletes in relation to painkillers.